Effects of Telerehabilitation on Pain and Disability in Patients with Chronic Neck Pain: A Systematic Review and Meta-Analysis. - Valenza-Pena, Geraldine; Calvache-Mateo, Andrés; Valenza, Marie Carmen; Granados-Santiago, María; Raya-Benitez, Julia; Cabrera-Martos, Irene; Díaz-Mohedo, Esther (MDPI, 2024)
This systematic review and meta-analysis explores the effectiveness of telerehabilitation in patients suffering from chronic neck pain, specifically on pain and disability. The research delves into an area of growing significance within the realm of healthcare, aiming to understand the impact of digital interventions on the rehabilitation process for individuals with prolonged neck pain. (2) Methods: The comprehensive review encompasses a wide array of studies evaluating the collective outcomes of numerous trials focused on telerehabilitation strategies. In this systematic review, PubMed/MEDLINE, Scopus, and Web of Science databases were systematically searched to identify studies on telerehabilitation's impact on pain. (3) Results: Eight studies met the inclusion criteria. Using the Downs and Black quality assessment, three studies were classified as good and five as fair. The authors identify specific modalities within telerehabilitation, such as remote exercise programs and virtual consultations, that contribute significantly to positive patient outcomes. Meta-analysis indicated a significant overall effect of telerehabilitation on pain reduction (MD = -1.27; 95% CI = -2.06; -0.47; p = 0.002). These findings support telerehabilitation's efficacy in pain management. (4) Conclusions: The synthesis of evidence presented in this systematic review and meta-analysis underscores the potential of telerehabilitation as an effective and accessible means of managing chronic neck pain, offering valuable insights for both healthcare practitioners and policymakers in advancing patient-centered care.
Keywords: Telemedicina; Cervicalgia - Fisioterapia; Telerehabilitation; Chronic neck pain